Reduced Rate of Repeated Prostate Biopsies Observed in ConfirmMDx Clinical Utility Field Study. - Wojno, Kirk J.; Costa, Frank J.; Cornell, Robert J.; Small, Jeffrey D.; Pasin, Erik; Van Criekinge, Wim; Bigley, Joseph W.; Van Neste, Leander (American Health & Drug Benefits, 2014)
Background: The diagnosis of prostate cancer is dependent on histologic confirmation in biopsy core tissues. The biopsy procedure is invasive, puts the patient at risk for complications, and is subject to significant sampling errors. An epigenetic test that uses methylation-specific polymerase chain reaction to determine the epigenetic status of the prostate cancer–associated genes GSTP1, APC, and RASSF1 has been clinically validated and is used in clinical practice to increase the negative predictive value in men with no history of prostate cancer compared with standard histopathology. Such information can help to avoid unnecessary repeat biopsies. The repeat biopsy rate may provide preliminary clinical utility evidence in relation to this assay’s potential impact on the number of unnecessary repeat prostate biopsies performed in US urology practices. Objective: The purpose of this preliminary study was to quantify the number of repeat prostate biopsy procedures to demonstrate a low repeat biopsy rate for men with a history of negative histopathology who received a negative epigenetic assay result on testing of the residual prostate tissue. Methods: In this recently completed field observation study, practicing urologists used the epigenetic test called ConfirmMDx for Prostate Cancer (MDxHealth, Inc, Irvine, CA) to evaluate cancer-negative men considered at risk for prostate cancer. This test has been previously validated in 2 blinded multicenter studies that showed the superior negative predictive value of the epigenetic test over standard histopathology for cancer detection in prostate biopsies. A total of 5 clinical urology practices that had ordered a minimum of 40 commercial epigenetic test requisitions for patients with previous, cancer-negative biopsies over the course of the previous 18 months were contacted to assess their interest to participate in the study. Select demographic and prostate-screening parameter information, as well as the incidence of repeat biopsy, specifically for patients with a negative test result, was collected and merged into 1 collective database. All men from each of the 5 sites who had negative assay results were included in the analysis. Results: A total of 138 patients were identified in these urology practices and were included in the analysis. The median age of the men was 63 years, and the current median serum prostate-specific antigen level was 4.7 ng/mL. Repeat biopsies had been performed in 6 of the 138 (4.3%) men with a negative epigenetic assay result, in whom no evidence of cancer was found on histopathology. Conclusion: In this study, a low rate of repeat prostatic biopsies was observed in the group of men with previous histopathologically negative biopsies who were considered to be at risk for harboring cancer. The data suggest that patients managed using the ConfirmMDx for Prostate Cancer negative results had a low rate of repeat prostate biopsies. These results warrant a large, controlled, prospective study to further evaluate the clinical utility of the epigenetic test to lower the unnecessary repeat biopsy rate.